“Para as ondas do mar sagrado”: uma etnografia dos rituais de rezadeiras e rezadores de Delmiro Gouveia, sertão de Alagoas. - Santos, Sergiana Vieira dos (2018)
Bringing rituals to the surface on the basis of anthropological analysis is not an easy task. For decades rituals have been researched and analyzed as phenomenon distanced from everyday, always with an approach focused on the opposition between magic and religion. After these decades the analysis of rituals today is extended to everyday situations without there being a separation of the activities that make up the day to day. The ritual practices of the female faith healers of Delmiro Gouveia, the Alagoas sertão, women and men of the country that migrated to the city demonstrate in the act of praying in people that their practices also underwent transformations. We transcribe two rituals in full to demonstrate how the relationship between them is distinct but, if they resemble in some respects, how a communitas do existential type (TURNER, 1974) can be perceived and how the emergency situation of therapeutic healing is, in most cases, the main reason for the search for female faith healers in this city. During the year 2016 and until the middle of 2017 through participant observation, identification cards and interviews recorded in audio, indispensable resources for the construction of this ethnography, we built relationships with the interlocutors, main characters of this plot of real life. Thus, we conclude that it is like a mighty river always in movement that the rituals here ethnographed are constituted and reconstructed. The works of Victor Turner (1974), Oliveira (1988), Oliveira (1985), Tambiah (1985), Harner (1980), Langdon (1996), Martins (2009) among others, authors mostly anthropologists, gave scientific support with their theories for this ethnography to be carried out.